The Subjective Quality of Life (SQOL) in Gastroenterological Patients - Jokić-Begić, Nataša; Tadinac, Meri; Hromatko, Ivana; Lauri Korajlija, Anita (2007)
The aim of this study was to assess the subjective quality of life and to identify the psychosocial predictors of SQOL among patients with a variety of gastroenterological diseases. A convenience sample of 78 gastroenterological patients completed questionnaires measuring subjective quality of life, perceived social support, coping style, depression and anxiety. The mean level of SQOL was 73%. Participants with a low level of subjective well-being (<50%) were more depressive (p<.001), had higher levels of both trait and state anxiety (p<.01), felt they received less social support from both friends and family (p<.01), and used avoidance as a coping strategy more often than patients with normal level of SQOL (p<.01). In three of four domains measured by the WHOQOL-BREF questionnaire – psychological, social and environmental - the subgroup of dissatisfied patients obtained significantly lower results, while in the domain of physical health the two subgroups did not differ. Multiple regression analysis showed the trait-anxiety to be the most important predictor for the subjective QOL. The group of patients remained within the normal range of subjective well-being expected by the homeostatic model, showing that gastroenterological disease alone does not result in a homeostatic failure. Psychological variables, especially the anxiety level and perceived satisfaction with the environment, play a major role in maintaining the homeostatic balance. This finding suggests the importance and necessity of psychological support in treatment of physical illnesses.
Projekt MZOS
Projekt MZOS
ENG